Von Tsingtau nach Qingdao. City Tour. - Kunzmann, Klaus R.; Zhan, Erpeng (Taylor & Francis, 2019)
Qingdao is a thriving port city in the Shandong Province of the People's Republic of China, located on the shores of the Yellow Sea. Between 1897 and 1914, the city was a so-called German mandated territory, named Tsingtau. In 2018, Qingdao's population numbered approximately 9 million. The city is an important industrial centre in China and one of the ten biggest ports in the world. It is a centre of advanced maritime sciences and technology research and development, a UNESCO city of film, a much-favoured tourist city and, not to forget, the production site of the famous Tsingtao beer, offered in Chinese restaurants all over the world. The German history of the city is still visible and is well protected. In contrast to many other cities in China, the old city centre of Qingdao has been fully preserved. The "German" conservation area along the beach is an attractive place for local citizens as well as for Chinese honeymooners and tourists from overseas.
Keywords: Stadtentwicklungsplanung; Stadtgeschichte; Architekturgeschichte; Hafenstadt; Industrialisierung; Wirtschaftspolitik; Metropole; Standort; Attraktivität; Tourismus; Hochschule; Urbanität; Nachhaltigkeit; Kolonialzeit; Stadtporträt